Implementation of monitoring and evaluation of BPI Bandung high school library - Devira Nurhaliza Zein; Angga Hadiapurwa; Yayu Wulandari; Diemas Arya Komara (Universitas Wijaya Kusuma Surabaya, 2023)
In its management, the library must be carried out monitoring and evaluation activities to see whether it has met the information needs of the people in the organization or institution. This monitoring and evaluation activity can be in the form of an assessment of services, collections, facilities, infrastructure, and library staff. Here I chose the BPI Bandung High School library as my place to conduct monitoring and evaluation activities on its collections. This research aims to monitor and evaluate the BPI Bandung High School library groups using the Formative-Sumative model. The method used is a descriptive qualitative approach. The techniques used are observation, interview, and documentation techniques. This research concludes that the BPI Bandung High School library is by the standard library criteria in Indonesia. It's just that the collection procurement and stock-taking can be maximized again.